PREDIKSI KETIDAKSTABILAN LERENG BERDASARKAN DATA HYDROLOGY MONITORING - -, Supandi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2013)
Mining activities have a high risk which one of them is the slope stability. Nature provides information about slope instability indication in various ways and methods. Observing indication of instability based on incidents that have occurred is an important study for improvement. One thing to do is viewing the correlation between groundwater position before and after the landslide that by knowing its behavior, the preventive measures against this potential can be reduced or eliminated. Groundwater monitoring installation is commonly done because this data is contributed to the slope stability analysis. Optimizing all existing data sources for various purposes are required to achieve effectiveness and job efficiency. The study was conducted by observing the behavior of groundwater level before the landslide occurred so that it can be deduced correlation between these two things. In this study, ground water level is observed at the closest point to the location of landslide that can reflect the real correlation. Groundwater level observation data were plotted into graphs and combined with related data such as rainfall intensity. Observational data groundwater levels and precipitation associated with the landslide incident can be obtained before the ground water level behavior occur landslide. Plotting generate a form of